A comparison of Asian e-government websites quality: using a non-parametric test. (1st January 2011) - Dominic, P.D.D.; Jati, Handaru; Sellappan, P.; Nee, Goh Kim
This research conducts tests to measure the quality of e-government websites of five Asian countries via web diagnostic tools online. We propose a methodology for determining and evaluating the best e-government website based on many criteria of website quality, consisting of linear weightage model (LWM), analytical hierarchy process (AHP), fuzzy analytical hierarchy process (FAHP), and one new hybrid model (NHM). This NHM has been implemented using combination FAHP and LWM to generate the weights for the criteria which are better and more fairly preferred. The results of this study confirmed that most Asian websites are neglecting in performance and quality criteria. By applying the hybrid model approach it has resulted in significant acceleration of implementation, raised the overall effectiveness and enabled more efficient procedure. To compare the ranking methods, a combination of Friedman's test and Dunn's multiple comparison procedure is adopted. When applied to the methods presented here, these tests indicate that AHP, FAHP, and Hybrid method methods perform better than LWM.